An Analysis of Student Errors and the Effect of Scaffolding in Solving Math Problems on StatisticalÂ Subject - Mufti Nida Uliya; Arjudin; Dwi Novitasari; Ketut Sarjana (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
This study aims to describe the types of error experienced by students by referring to indicator of errors by Kastolan theory, scaffolding that can reduce student errors, and how scaffolding test affects student. This type of study is qualitative study. The subjects in this study were 4 students. The selection of subjects used simple random sampling technique. The instruments used were test instruments and interview guidelines. The data analysis technique uses the application model of Miles & Huberman’s theory: 1) Data collection, 2) Data condensation, 3) Data display, 4) Drawing and verifying conclusions. The results showed: 1) The errors experienced by students when working on test questions included three types of errors, namely conceptual error, procedural error, and technique error. The percentage of students who made conceptual errors was 35.7%, students who made procedural errors were 54.8%, and students who made technical errors were 38.1%; 2) From the application of scaffolding to 4 research subjects who committed 3 types of errors, it was obtained that conceptual errors were more suitable given scaffolding level 2, which is explaining: showing and telling. While procedural errors are more suitable given scaffolding level 2, which is explaining: telling. In the scaffolding technique errors that are suitable are level 1 scaffolding, which is reviewing: interpreting students actions; 3) After being given scaffolding, the errors made by students were significantly reduced from before being given scaffolding.